Mitochondrial pathway mediated apoptosis and cell cycle arrest triggered by cobalt(III) complex in Dalton’s lymphoma cells - Praveen Kumar Verma, Mannu Kumar Gond, Manoj Kumar Bharty, Arbind Acharya (Journal of Applied Pharmaceutical Science, 2021)
Cancer is a group of diseases which evolves from uncontrolled growth of abnormal cells. It has become the second leading cause of death worldwide. Many platinum-based compounds like cisplatin and carboplatin are widely used as a therapeutic approach against cancer, but patients are resistant to these therapeutic agents with life-threatening side effects. In this study, we used a non-platinum-based compound, i.e. cobalt complex, on the Dalton’s lymphoma cells (DL cells). It is a tumor model of murine T-cell lymphoma of thymic genesis, which is very aggressive. The present study was focused on evaluating the anticancer efficacy of cobalt complex on DL cells. The IC50 value of cobalt complex was found to be 80 ±3.21 μM in DL cells’. In addition, cobalt complex promoted condensed nuclei, G1 phase arrest, and induced early and late apoptotic cells. Additionally, flow cytometry examination showed a significant loss in mitochondrial membrane potential and induction of reactive oxygen species after treatment. Furthermore, Western blot revealed the increased p53, cyt-c, Bax protein, and decreased Bcl2 protein level in treated DL cells. These results verified the anticancer properties of cobalt(III) complex against DL cells and propose an alternative therapeutic drug in cancer treatment.
Keywords: Anti-tumor activity, apoptosis, cobalt complex, Dalton’s lymphoma, reactive oxygen species.